G354(P) Are unnecessary fluid challenges slowing the flow of a&e departments?. (12th March 2018) - Coles, S; Malley, M
Abstract : Aims: Fluid challenges are a common tool used in A and E to aid decision-making. As they can often prove time-consuming, we aimed to assess whether they impacted on the 4 hour breech target at a busy district general hospital (DGH) paediatric A and E, and whether their use was always indicated. Methods: We analysed all 4 hour breeches at a busy DGH paediatric A and E over a 24 day period in December 2016. We attempted to identify those breeches which followed an oral fluid challenge initiated by medical staff and documented in the A and E notes. We then assessed whether this cohort of patients showed the following objective signs of dehydration on presentation (from NICE guidelines): tachycardia, tachypnea, decreased skin turgor and decreased urine output. We conducted a literature search to identify evidence supporting the use of fluid challenges. Results: Of 294 breeches, 36 (12.1%) cases involved fluid challenges. Of these, 86% were discharged home. Half of the children who breeched awaiting completion of a fluid challenge had no objective signs of dehydration recorded on presentation. A further third recorded only tachycardia, although many of these were febrile. Of those with no recorded signs of dehydration, 11% were admitted to the paediatric assessment unit for ongoing observation. Of the 5 patients admitted, two had 2 or more signs of dehydration whilst 2 exhibited no characteristic symptoms. Our literature search revealed no high quality evidence for the use of fluid challenges as a reliable diagnostic aid. Conclusion: Fluid challenges were implicated in a significant proportion of all paediatric breeches, half of which recorded no core objective signs of dehydration on presentation. We would therefore suggest this cohort did not require a fluid challenge yet accounted for over 6% of all departmental breeches. No strong evidence supports their use. We advocate a more judicious use of fluid challenges limited to the small proportion of children showing objective signs of mild or moderate dehydration at presentation where their use may provide greater decision-making power. This may help reduce breeches at the busiest time of year. A larger scale study would provide with more information to further our conclusions.